Good Clinical Outcome Decreases With Number of Retrieval Attempts in Stroke Thrombectomy: Beyond the First-Pass Effect. Issue 2 (February 2021) - Flottmann, Fabian; Brekenfeld, Caspar; Broocks, Gabriel; Leischner, Hannes; McDonough, Rosalie; Faizy, Tobias D.; Deb-Chatterji, Milani; Alegiani, Anna; Thomalla, Götz; Mpotsaris, Anastasios; Nolte, Christian H.; Fiehler, Jens; et al.
Abstract : Background and Purpose: Endovascular therapy is the standard of care in the treatment of acute ischemic stroke due to large-vessel occlusion. Often, more than one retrieval attempt is needed to achieve reperfusion. We aimed to quantify the influence of endovascular therapy on clinical outcome depending on the number of retrievals needed for successful reperfusion in a large multi-center cohort. Methods: For this observational cohort study, 2611 patients from the prospective German Stroke Registry included between June 2015 and April 2018 were analyzed. Patients who received endovascular therapy for acute anterior circulation stroke with known admission National Institutes of Health Stroke Scale score and Alberta Stroke Program Early CT Score, final Thrombolysis in Cerebral Infarction score, and number of retrievals were included. Successful reperfusion was defined as a Thrombolysis in Cerebral Infarction score of 2b or 3. The primary outcome was defined as functional independence (modified Rankin Scale score of 0–2) at day 90. Multivariate mixed-effects models were used to adjust for cluster effects of the participating centers and confounders. Results: The inclusion criteria were met by 1225 patients. The odds of good clinical outcome decreased with every retrieval attempt required for successful reperfusion: the first retrieval had the highest odds of good clinical outcome (adjusted odds ratio, 6.45 [95% CI, 4.0–10.4]), followed by the second attempt (adjusted odds ratio, 4.56 [95% CI, 2.7–7.7]), and finally the third (adjusted odds ratio, 3.16 [95% CI, 1.8–5.6]). Conclusions: Successful reperfusion within the first 3 retrieval attempts is associated with improved clinical outcome compared with patients without reperfusion. We conclude that at least 3 retrieval attempts should be performed in endovascular therapy of anterior circulation strokes. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03356392. Abstract : Supplemental Digital Content is available in the text.